Mental health matrix support in Primary Care: a critical review (2000-2010) - Athié, Karen (2013)
Objective: A critical review of articles published between 2000 and 2010 on the relation between mental health and primary care in Brazil in view of the practice of matrix support. Method: Review of virtual database in the period in question. The descriptors were “mental health”, “primary care”, “matrix support”, and the analysis categories were constructed from the reading of the articles. Results: We selected 86 articles, divided in three categories: the articulation analyzed from the Mental Health, the Primary Care Health, and experiences of matrix support. This analysis revealed the existence of different ways of describing the collaborative care. Conclusions: The Brazilian experience is in line with global recommendations towards decreasing the gap between the offer and treatment needs care. The construction of the integrated mental health network for Family Health Strategy is a new challenge for the Brazilian Psychiatric Reform.